Efficacy and Safety of Prostatic Artery Embolization in the Treatment of High Risk Benign Prostatic Hyperplasia and its Influence on Postoperative Life Quality of Patients - Wang, Kun; Chen, Ming; Liu, Yiqing; Xiao, Weiren; Qian, Yonghong; Liu, Xu (Frontiers in Surgery, 2022)
Objective: to evaluate the efficacy, safety and postoperative quality of life of high risk benign prostatic hyperplasia (BPH) patients treated with prostatic artery embolization. Methods: Thirty-four patients diagnosed as high-risk BPH in our hospital from January 2020 to June 2021 were selected. All patients received prostatic artery embolization for the treatment of BPH. The changes of international prostate symptom score (IPSS), prostate volume (PV), remaining urine (RU), maximum urine flow rate (Qmax), quality of life scale -74(GQOLI-74), time to sleep without disturbance (HUS) judgment, self-rating anxiety scale (SAS) score and self-rating depression scale (SDS) score before operation and 1 and 6 months after operation were compared. Results: All the 34 patients of prostatic artery embolization were successful, including unilateral embolization in 15 cases and bilateral embolization in 19 cases, a total of 53 prostatic arteries were embolized. No serious complications occurred in the patients after surgery. The IPSS, PV, and RU levels of the patient at 1 and 6 months after surgery were lower than those before surgery and significantly lower at 6 months after surgery than at 1 month after surgery (P<0.05). Qmax levels at 1 and 6 months after surgery were higher than before surgery and significantly higher at 6 months after surgery than at 1 month after surgery (P<0.05). Six months after surgery, the scores of psychological function, social function, material life and physical function of GQOLI-74 were significantly higher than those before surgery (P<0.05). The HUS of the patient six months after surgery was significantly increased, and the SAS and SDS scores were significantly decreased as compared with those before surgery (P<0.05). Conclusion: For high-risk patients with BPH, prostate embolization is an effective and safe method, which can significantly improve the quality of life of patients after surgery and has good application prospects.